Prevalence of Malocclusion of Deciduous Dentition in Dogs: An Evaluation of 297 Puppies. (December 2019) - Hoyer, Naomi K.; Rawlinson, Jennifer E.
A total of 297 dogs between 8 and 12 weeks of age were examined during a 1-year period to evaluate occlusion. Dogs were categorized either as individual dogs or members of a litter and purebred or mixed breed. Occlusion was evaluated by class: normal, class 1 malocclusion (MAL1), class 2 malocclusion (MAL2), or class 3 malocclusion (MAL3). Dogs with MAL3 were also subdivided based on whether MAL3 was considered a breed standard; dogs with breed standard MAL3 were considered under normal occlusion for statistical analyses. Malocclusions were further categorized as mild, moderate, or severe. Twenty-six percent (77/297) were identified as having a malocclusion. For single dogs, purebreds had a significantly higher percentage of malocclusions compared to the mixed breeds (33.8% and 20% respectively; P = .042). For dogs in litters, there were no purebreds with malocclusion, which was significantly less than the number of mixed breeds with malocclusions (0% and 23.5%, respectively; P = .0023). No significant difference in prevalence was noted between mixed breed and purebred dogs. Occlusal evaluation is important for all dogs to allow for early recognition of malocclusion and, if necessary, intervention in a timely manner.